Glutathione Mediates Growth Regulation of Chickpea Plant Cicer arietinum and Mitigates Salinity Stress. - Al-Kazzaz, Amel Ghanim Muhmood; Al-Hayany, Eman Hussain; Attarbashi , Rahaf Wail; Phanom Sutthisaksopon (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Glutathione is water-soluble with a low molecular weight and is commonly spread in plants. It is a co-factor in several biochemical reactions and acts together with signaling molecules and hormones, and its redox state activates signal transduction. The experiment was conducted in the botanical garden, Department of Biology, College of Education for Pure Sciences, Ibn Al- Haitham, University of Baghdad, during the growing season 2020-2021 to evaluate the potential effects of foliar spraying with (25, 50, 75 mg.L-1) glutathione in addition to the control (0) on the growth of chickpea plants subjected to sodium chloride salt (100, 200 mM.L-1) addition to the control (0). The results point out that salinity clearly decreased, as did plant height, branch number, shoot dry weight, nitrogen, phosphorus, potassium concentration, protein percentage, and increased sodium concentration in chickpea plants. A foliar spray of Glutathione, notably 50 and 75 mg.L-1, enhanced the tolerance of chickpea plants by improving growth traits.